Stiffness of the Gastrocnemius–Achilles Tendon Complex Between Amateur Basketball Players and the Non-athletic General Population - Chang, Tian-Tian; Li, Zhe; Wang, Xue-Qiang; Zhang, Zhi-Jie (Frontiers in Physiology, 2020)
Muscle and tendon stiffness are related to sports performance, tendinopathy, and tendon degeneration. But the effects of habitual loading on muscle and tendon mechanical properties are unclear. Using amateur basketball players as examples, we investigated the effects of mechanical loading on the stiffness of gastrocnemius-Achilles tendon (AT) complex in non-dominant and dominant lower limbs. Then we evaluated the correlation between gastrocnemius and AT stiffness. Forty participants (20 amateur basketball players; 20 normal nonathletic persons) were recruited for this study. Stiffness of the gastrocnemius-AT complex was assessed using MyotonPRO at neutral position and 10° dorsiflexion of the ankle joint in participants from amateur basketball players and the nonathletic general population. Our results showed a greater stiffness of gastrocnemius-AT complex in amateur basketball players than in healthy nonathletic subjects at neutral position and 10° dorsiflexion of the ankle joint (P＜0.05). No significant difference in stiffness was found between non-dominant and dominant lower limbs either in amateur basketball players or in generally healthy subjects (P＞0.05). A significant positive correlation was obtained between stiffness of the AT and medial gastrocnemius (MG) in amateur basketball players (neutral position: r=0.726 and p=0.001; dorsiflexion 10°: r=0.687 and p=0.001). The amateur basketball players exhibit significantly higher stiffness value in Achilles and gastrocnemius. This is possibly caused by repeated training effects. The symmetric stiffness of AT and gastrocnemius exists both in amateur basketball players and generally healthy subjects. A significant correlation between the AT and the MG was found in amateur basketball players.